Morphometric assessment of hip dysplasia in a cat treated by juvenile pubic symphysiodesis - Lai, Alen; Culvenor, John; Bailey, Craig (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objective: To quantitatively evaluate the change of the coxofemoral joints using computed tomography and distraction index in a cat with hip dysplasia treated by juvenile pubic symphysiodesis.Study Design: Case report.Animal: Eighteen-week-old female entire Maine Coon cat.Results: Juvenile pubic symphysiodesis resulted in changes in the distraction index, acetabular angle, dorsal acetabular rim angle, dorsal acetabular sector angle, and clinical improvement at the six month follow-up. No intra-operative or postoperative complications were recorded.Conclusions: Juvenile pubic symphysiodesis performed at 18 weeks of age resulted in improvement in hip joint conformation and hip laxity in a dysplastic cat.Clinical relevance: Juvenile pubic symphysiodesis may be a promising treatment for feline hip dysplasia and is a safe and technically simple procedure to perform. Further investigations are warranted.
Keywords: Feline; cat; hip dysplasia; computed tomography; JPS; juvenile pubic symphysiodesis; morphometric assessment